Freedom and responsibility: Christian and Muslim explorations - Sinaga, Martin L.; Sinn, Simone (Lutheran University Press, 2010)
Freedom and responsibility : joint theological explorations by Christians and Muslims : challenges today / Mark N. Swanson -- Freedom and responsibility : an Islamic perspective / Amina Wadud -- Law, freedom, and responsibility in Christianity and Islam / Oddbjorn Leirvik -- Foundations for freedom and religious freedom in the Qur'an / Sahiron Syamsuddin -- The freedom of a Christian according to Evangelical Lutheran theology / Hans-Peter Grosshans -- Freedom and responsibility in society / Ignas Kleden -- Freedom, responsibility and shame in Indonesia / Bernard Adeney-Risakotta -- Women's freedom and responsibility in Islam : a brief review of texts and contexts in Indonesia / Siti Syamsiyatun -- Freedom of religion or belief in Indonesia and the challenge of Muslim exceptionalism / Suhadi Cholil -- Vox Helveticorum-vox Dei? : the Swiss ban on the construction of minarets : acid test for Christian-Muslim relations / Reinhold Bernhardt